Relatório de Estágio Profissional - "Ser professor: Carinho, Competência e Compromisso" - Diogo Porfirio Nunes Fernandes (2018)
This report covers a year of experiences and learning from a student and intern (author) in a school in Gondomar, Porto. Given that the internship is one of the most important parts of the professional training, it's important to look back and analyse the knowledge acquired during this stage, as well as reflecting on the learning done during the day to day of the school program. This document is structured in 6 chapters: (1) Introduction - where we explain how the document is organized; (2) Author's background - where you can learn about the author; (3) Institutional background - where you can learn about the internship and the school where it happened; (4) Operational background - divided in 3 areas explaining the role of the Physical Education teacher at school, from the sports hall, to the class board, and the never ending search for knowledge; (5) Research study - research about the motivation of students in the Physical Education class and strategies to increase their willingness to practice sports; (6) Learnings from my experience as student and intern and analysis of past and future directions; (7) Bibliographic references and attachments.